Meningkatkan Kemampuan Berpikir Logis Anak Usia 4-5 Tahun Melalui Kegiatan Berkebun Di TK Azalia - Widari, Ida; Sumiati, Ai (Jurnal Pendidikan Islam Anak Usia Dini : Anaking, 2025)
In my research, it has been proven that the logical thinking ability of early childhood children in Azalia Kindergarten, Cisurupan District, is relatively low. This can be seen from the lack of concentration of children in understanding the concept of logical thinking. Therefore, I want to improve the logical thinking ability in Azalia Kindergarten. The obstacle faced is the lack of Educational Game Tools (APE), which causes the learning process to be monotonous. Furthermore, as a researcher, I will go directly to the field to better understand how to implement effective learning for children aged 4-5 years. Initial observations will be conducted on Wednesday, February 20, 2025, to assess the logical abilities of children in Azalia Kindergarten, Cisurupan District. In daily activities at school, we only provide naku for writing and similar activities. I will use the Kemmis method in this study, with eight participants, consisting of four girls and four boys.  Keywords Logical thinking Early childhood Media gardening activities